2018
DOI: 10.1016/j.ultsonch.2017.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Single, simultaneous and sequential applications of ultrasonic frequencies for the elimination of ibuprofen in water

Abstract: The study is about the assessment of single and multi-frequency operations for the overall degradation of a widely consumed analgesic pharmaceutical-ibuprofen (IBP). The selected frequencies were in the range of 20-1130kHz emissions coming from probes, baths and piezo-electric transducers attached to plate-type devices. Multi-frequency operations were applied either simultaneously as "duals", or sequentially at fixed time intervals; and the total reaction time in all operations was 30-min. The work also covers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…While ultrasound is known as a clean AOP that does not require the addition of any chemical, the main drawbacks of this method are high energy consumption and long reaction times [30] . Accordingly, studies have been aiming to address these issues by finding the optimum condition via investigation of different parameters such as the sonication frequency and power [31] , [32] , or combining ultrasound with other AOPs or other ultrasound frequencies to enhance the efficiency of the process by the possible synergy [33] , [34] , [35] . Considering that combining multiple ultrasound frequencies requires the addition of no chemicals, since the early 2000 s, there has been an increase in the investigation of the possible advantages that simultaneous application of multiple frequencies might have over single-frequency ultrasound (SFUS).…”
Section: Introductionmentioning
confidence: 99%
“…While ultrasound is known as a clean AOP that does not require the addition of any chemical, the main drawbacks of this method are high energy consumption and long reaction times [30] . Accordingly, studies have been aiming to address these issues by finding the optimum condition via investigation of different parameters such as the sonication frequency and power [31] , [32] , or combining ultrasound with other AOPs or other ultrasound frequencies to enhance the efficiency of the process by the possible synergy [33] , [34] , [35] . Considering that combining multiple ultrasound frequencies requires the addition of no chemicals, since the early 2000 s, there has been an increase in the investigation of the possible advantages that simultaneous application of multiple frequencies might have over single-frequency ultrasound (SFUS).…”
Section: Introductionmentioning
confidence: 99%
“…Wei et al [126] reported that ultrasonic irradiation activated persulphate for the degradation of carbamazepine, dioxines, trichloroethane and bisphenol A, both with and without thermal activation. The elimination of ibuprofen in water has been well addressed in the sequential use of ultrasonic frequencies, as reported by Ziylian-Yavas et al [121].…”
Section: Sonolysis (Ultrasound (Us) Radiation)mentioning
confidence: 90%
“…Lianou et al [120] degraded piroxicam from ultrapure water using different power densities. Ziylan-Yavas et al [121] succeeded in the degradation of ibuprofen from ultrapure water with the application of various single ultrasonic frequencies. Serna et al [122] degraded oxacillin from distilled water at 275 kHz.…”
Section: Sonolysis (Ultrasound (Us) Radiation)mentioning
confidence: 99%
“…All single and hybrid AOP’s were carried out in a high-frequency plate-type ultrasonic reactor with a 120 W generator (operated at 90% capacity) connected to three piezoelectric transducers (22 cm 2 ) that emitting at 577 kHz (Ultraschall/ Meinhardt, Germany). The solution temperature in the reactor was maintained at 25 ± 0.5 °C by water circulation, and the power density was kept constant at 0.23 W mL −1 (determined by calorimetry) as reported in a previous work [28] . The light source in UV-supported AOP’s was a low-pressure mercury UV-lamp emitting monochromatically at 253.7 nm and operated at an intensity of 4.7 W m −2 .…”
Section: Methodsmentioning
confidence: 99%